2020
DOI: 10.1088/1361-6528/ab622f
|View full text |Cite
|
Sign up to set email alerts
|

High-aspect-ratio iron nanowires: magnetic field-assisted in situ reduction synthesis and extensive parametric study

Abstract: High-performance iron nanowires have attracted wide attention from researchers due to their 'controllable' arrangement distribution by magnetic fields. In this paper, a simple magnetic field assisted in situ reduction method was proposed to synthesize Fe NWs with high aspect ratio, smalldiameter, and good dispersion. A detailed parametric study determining the relationship among the final morphologies of the products and magnetic field, injection sequence of sodium borohydride that was injected into ferrous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…High-aspect-ratio Fe NWs were synthesized according to our previously reported method [ 19 ]. First, 2.78 g of FeSO 4 ·7H 2 O and 5.30 g of NaBH 4 were separately dissolved in 100 mL of pure water to prepare solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-aspect-ratio Fe NWs were synthesized according to our previously reported method [ 19 ]. First, 2.78 g of FeSO 4 ·7H 2 O and 5.30 g of NaBH 4 were separately dissolved in 100 mL of pure water to prepare solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Further, in addition to the characteristics of metal nanowires themselves, the filling ratio of metal nanowires also has a great impact on the sensing performance, but little attention has been paid to it [ 13 , 14 ]. Studies have explored the mechanism of the synthesis of Fe NWs by the magnetic field-assisted in situ reduction method [ 19 ], mastered the method of controlling the aspect ratio of Fe NWs, and studied their potential application in electromagnetic absorption [ 20 ]. It was found that the high aspect ratio of Fe NWs is beneficial for obtaining a good conductive network with a low filling mass fraction.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional wire-like Fe has the advantages of a small size and the large specific area, which can improve the anisotropy and resonance frequency of magnetic materials [51]. For example, Fe nanofibers, Fe nanowires, Fe nanochains, etc., all have good microwave absorption performance and are the focus of current research.…”
Section: Wire-like Fementioning
confidence: 99%
“…To achieve the objectives outlined above, we synthesized monodisperse Fe NWs with a high aspect ratio using the procedure described in our previous report. 26 We deposited a series of anhydrous ethanol dispersions with different contents of Fe NWs on polyethylene terephthalate (PET) substrates using the drop-coating method. With the help of a Halbach array of magnets, we formed an ordered structure of Fe NWs.…”
Section: Introductionmentioning
confidence: 99%